2015
DOI: 10.1186/s12889-015-1922-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with DELAY in diagnosis among tuberculosis patients in Hohoe Municipality, Ghana

Abstract: BackgroundAny delay in diagnosis and consequently treatment of TB patients not only increases the infectivity of the disease in the community, but may also lead to more advance disease state, which may result in more complications and expose patients to higher risk of death. The aim of this study was to assess delays in diagnosing new TB patients and the factors associated with these delays in Hohoe Municipality of Ghana.MethodsA cross sectional study was carried out among 73 new TB Patients, 15 years or older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
72
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 24 publications
16
72
4
6
Order By: Relevance
“…This was in agreement with a previous study that found rural residence as a risk factor of patient delay for TB diagnosis [13,27]. Previous studies documented HIV-positive individuals to have less patient delay compared to HIV-negative [12,28]. Previous studies have noted that HIV-positive individuals are more likely to suffer serious TB symptoms which prompt them to seek care earlier than HIV-negative individuals [26,28].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This was in agreement with a previous study that found rural residence as a risk factor of patient delay for TB diagnosis [13,27]. Previous studies documented HIV-positive individuals to have less patient delay compared to HIV-negative [12,28]. Previous studies have noted that HIV-positive individuals are more likely to suffer serious TB symptoms which prompt them to seek care earlier than HIV-negative individuals [26,28].…”
Section: Discussionsupporting
confidence: 82%
“…By the time of enrolment the patient could have had several diagnostic visits to the clinic where the current TB diagnosis was made, as well as sought care from several health services providers. For these reasons as well as the wide variation in literature about patient delay for TB diagnosis [6,7,8,9,10,11,12,13,14], we operationalized long delay to be ! 60 days with TB symptoms before TB diagnosis before TB diagnosis before current study data analysis.…”
Section: Operational Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, despite this substantial delay, Qatar seems to compare favorably with both developed and developing countries with regard to the median total diagnostic delay. For example, the median total delays of PTB diagnosis in New York (USA), France, Norway, and Turkey are 57, 68, 63, and 49 days, respectively,[10111213] while in Ethiopia, Nepal, and Ghana are 80, 60, and 104, respectively[141516] with the highest median delay of 126 days reported in Tanzania. [4] Nevertheless, data from each of these countries may not necessarily represent the entire country, and the significant delay in PTB diagnosis in Qatar (despite the highly effective National TB Program and the free high standard public health system) remains striking.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic and treatment delays contribute to increased TB transmission and severity of illness [3]. Delay in diagnosis and treatment of TB has been studied in various parts of the world.…”
Section: Introductionmentioning
confidence: 99%